MCDA Spatial Approach for Flood Disaster Vulnerability Assessment in Tulang Bawang Regency - Yanto, Nana Putri; Sahid, Sahid; Aziz, Fahmi; Mustofa, Asep Nurul Ajiid; Prizkanisa, Siti (Media Komunikasi Geografi, 2025)
Indonesia's location in a region prone to a variety of natural and societal disasters highlights the critical need of comprehending society's susceptibility to such events. Tulang Bawang Regency, located in Lampung Province, is vulnerable to various risks, particularly those associated with flood catastrophes. This research aims to assess the community's susceptibility in Tulang Bawang Regency to several types of catastrophes, focusing on social, economic, physical, and environmental factors. The research approach utilized combines the four primary aspects of vulnerability - social, physical, economic, and environmental - through the MCDA spatial method. The study on vulnerability to flood disasters in Tulang Bawang Regency shows that the most affected vulnerable population is in Dente Teladas District, particularly individuals of vulnerable age, residents in poverty, and people with disabilities. The assessment indicates that the Rawa Jitu District region has the highest levels of economic vulnerability, particularly in relation to poverty. The projected material losses from flooding are 23,125.11 million rupiah for physical damage and 50,356.32 million rupiah for economic losses. In addition, there is a possibility of substantial environmental harm in Tulang Bawang Regency, estimated at 35,508.18 hectares.